IMPLEMENTASI RESTORATIVE JUSTICE OLEH PENYIDIK TERHADAP TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA (Studi Kasus di Kepolisian Resor Trenggalek) - Ning Imas, Dhynar Mayank; Fahrazi, Mahfudz (MIZAN, Jurnal Ilmu Hukum, 2024)
This study examines the implementation of Restorative Justice by investigators against crimes of domestic violence (a case study at the Trenggalek resort police). The purpose of this study is to analyze the implementation of regulations related to crimes of domestic violence according to the perspective of normative law and the process of Restorative Justice for crimes of domestic violence committed by investigators at the Trenggalek District Police. This research method uses empirical legal research. The results of this study explain that in general the implementation of rules related to the crime of domestic violence according to the perspective of normative law, namely that it has been regulated as a lex specialist in Law Number 23 of 2004 concerning the Elimination of Domestic Violence, explains that "Violence in the Household is any act against a person, especially a woman, which results in physical, sexual, psychological misery or suffering, and/or neglect of the household including threats to commit acts, coercion, or unlawful deprivation of liberty within the household sphere. The process of Restorative Justice for crimes of domestic violence carried out by investigators from the Trenggalek Regency Resort Police, namely: After a preventive approach is taken between the victim and the perpetrator who agrees to make peace, the investigator will carry out a further level action plan, namely by holding a Restorative Justice Case, Conducting Termination of Investigation, Completing SP3 investigation administration (Warrant for Termination of Investigation), Sending SP3 Notification Letters to related parties (Reporter, Reported Party, and Trenggalek District Attorney), and reporting to the leadership. After these actions are deemed sufficient, the suspect will be released immediately.